1971
DOI: 10.1111/j.1365-2133.1971.tb14198.x
|View full text |Cite
|
Sign up to set email alerts
|

The Diurnal Variation of Water Vapour Loss From the Skin in Relation to Temperature

Abstract: SUMMARY.— The water vapour loss from irritated and non‐irritated skin sites was determined twice daily during a period of 19–42 days after the irritation. Diurnal variation of skin temperature gives anomalous values for water vapour loss but does not account for anomalous activation energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
3

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
1
11
1
3
Order By: Relevance
“…Both of these studies reported at least one TEWL peak around 4:00 p.m. Furthermore, Spruit[28] found that TEWL on the forearm skin was higher in the afternoon than in the morning. He suggested that the diurnal variation in TEWL of the skin is a function of diurnal variation in skin surface temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies reported at least one TEWL peak around 4:00 p.m. Furthermore, Spruit[28] found that TEWL on the forearm skin was higher in the afternoon than in the morning. He suggested that the diurnal variation in TEWL of the skin is a function of diurnal variation in skin surface temperature.…”
Section: Discussionmentioning
confidence: 99%
“…L'existence d'un rythme circadien de la PIE sur le visage et sur les avant-bras reste débattue [18,20,25,26,34]. Dans notre étude sur le cuir chevelu, il apparaît que le biorythme circadien de la PIE avait une ampleur importante, quoique inférieure à celle de l'excrétion instantanée du sébum.…”
Section: Discussionunclassified
“…La température cutanée, l'intensité de la sudation, le flux de sébum et le pH de la couche cornée sont eux aussi soumis à des fluctuations au cours du nycthémère [17][18][19][20][21][22][23][24][25][26]. Dans tous les cas, ces rythmes ne sont pas directement influencés par la lumière.…”
Section: Introductionunclassified
“…Spruit [19] found that transepidermal water loss on the forearm skin was higher in the afternoon than in the morning and Yosipovitch et al [6] found a circadian rhythm of transepidermal water loss with a peak in the late afternoon. In contrast, Reinberg et al [20] reported a circadian rhythm of transepidermal water loss on the forearm skin with a trough at 2 p.m. and a nocturnal peak.…”
Section: Discussionmentioning
confidence: 99%